Facile means for quantifying microRNA expression by real-time PCR - Rui Shi; Vincent L. Chiang (BioTechniques)
MicroRNAs (miRNAs) are 20–24 nucleotide RNAs that are predicted to play regulatory roles in animals and plants. Here we report a simple and sensitive real-time PCR method for quantifying the expression of plant miRNAs. Total RNA, including miRNAs, was polyadenylated and reverse-transcribed with a poly(T) adapter into cDNAs for real-time PCR using the miRNA-specific forward primer and the sequence complementary to the poly(T) adapter as the reverse primer. Several Arabidopsis miRNA sequences were tested using SYBR® Green reagent, demonstrating that this method, using as little as 100 pg total RNA, could readily discriminate the expression of miRNAs having as few as one nucleotide sequence difference. This method also revealed miRNA tissue-specific expression patterns that cannot be resolved by Northern blot analysis and may therefore be widely useful for characterizing miRNA expression in plants as well as in animals.